2006
DOI: 10.1080/01459740600686633
|View full text |Cite
|
Sign up to set email alerts
|

Dark Winter and the Spring of 1972: Deflecting the Social Lessons of Smallpox

Abstract: This article examines how the master status of bioterrorism has distracted professional and political attention from the social lessons of smallpox. I illustrate this by comparing an influential bioterrorism simulation known as Dark Winter with the social history surrounding the Yugoslavian smallpox epidemic of 1972. Dark Winter's epidemiological premises were largely based upon what was learned from the Yugoslavian outbreak. Yet, although this epidemic was non-deliberate, the exercise did not attend to the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Indeed, a commonly expressed concern is that the funding for biodefense is draining resources from other public health areas (Reppert, 2005). For instance, Barrett (2006) reports that ''in a survey of 539 local public health agencies, 53 percent reported that bioterrorism preparedness diverted significant resources away from such public health activities as prenatal care, STD prevention, and school immunization campaigns'' (National Association of County and City Health Officials, 2003, as cited in Barrett, 2006, p. 185). Leitenberg (2005) noted that ''currently one-third of both the National Institutes of Health (NIH) infectious disease budget and the Centers for Disease Control and Prevention (CDC) budget and more than half of U.S. Government and corporate vaccine development is relegated to biodefense, that is, it focuses on the 'select agents,' those pathogens that are considered most likely to be used as biological weapon agents'' (p. 66).…”
Section: Charting the ''Biodefense Bonanza'': Technological Solutionsmentioning
confidence: 99%
“…Indeed, a commonly expressed concern is that the funding for biodefense is draining resources from other public health areas (Reppert, 2005). For instance, Barrett (2006) reports that ''in a survey of 539 local public health agencies, 53 percent reported that bioterrorism preparedness diverted significant resources away from such public health activities as prenatal care, STD prevention, and school immunization campaigns'' (National Association of County and City Health Officials, 2003, as cited in Barrett, 2006, p. 185). Leitenberg (2005) noted that ''currently one-third of both the National Institutes of Health (NIH) infectious disease budget and the Centers for Disease Control and Prevention (CDC) budget and more than half of U.S. Government and corporate vaccine development is relegated to biodefense, that is, it focuses on the 'select agents,' those pathogens that are considered most likely to be used as biological weapon agents'' (p. 66).…”
Section: Charting the ''Biodefense Bonanza'': Technological Solutionsmentioning
confidence: 99%
“…There was a pneumonic outbreak in Ecuador in 1998, and two nosocomial (hospital-acquired) pneumonic cases in Peru in 2010 (Schneider et al 2014). Between 2000 and 2009, there were five natural pneumonic outbreaks affecting a dozen or more people: India (2002), Congo (2005 and2006), Uganda (2006), and China ( 2009) (Joshi et al 2009;Butler 2013;Bertherat et al 2011;and Wang et al 2010). The 2002 Indian outbreak in the Shimla district of Himachal Pradesh was caused by a strain distinct from the 1994 pneumonic epidemic in Surat (Kingston et al 2009).…”
Section: Plague Incidence and Causes Todaymentioning
confidence: 99%
“…Understanding these conditions-of settlement, social order, nutrition-are historical issues that science alone cannot address. If the human components of epidemics are not understood (or are misunderstood), then our expensive preparations for the future will fail to mitigate not only the widespread return of diseases like plague, but also new emerging infectious diseases (Barrett 2006). The long history of plague gives us the rare opportunity to study a single disease over an unprecedented period of time.…”
Section: Uniting the Study Of Past And Present For The Futurementioning
confidence: 99%
“…Understanding these conditions-of settlement, social order, nutrition-are historical issues that science alone cannot address. If the human components of epidemics are not understood (or are misunder stood), then our expensive preparations for the future will fail to miti gate not only the widespread return of diseases like plague, but also new emerging infectious diseases (Barrett 2006). The long history of plague gives us the rare opportunity to study a single disease over an unprec edented period of time.…”
Section: Uniting the Study Of Past And Present For The Futurementioning
confidence: 99%